Regulation of hnRNP A2/B1 and hnRNP K by synaptic activity and BDNF in the hippocampus - Leal, Graciano (2014)
Tese de doutoramento em Biociências, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra